Co-morbidity of down syndrome with autism spectrum disorder: Dental implications - A. Sultan, MDS; A. Juneja, MDS; S. Bhaskar (Elsevier, 2020)
Over the past several years, numerous studies have emerged documenting the high incidence (1-11%) of comorbidity of autism spectrum disorders (ASD) in Down syndrome (DS). While children with these health issues are reported to be more cognitively impaired presenting significantly lower IQ scores, they also demonstrate differences in social and expressive language skills when compared to their coequals with DS only. More than that subjects with DS and ASD comorbidity exhibit atypical behaviour manifested by stereotypic anxiety and social withdrawal when compared to DS alone.This article provides a brief understanding of this challenging concurrence along with a case report of a 12-year-old male patient with ASD-DS condition reporting with multiple missing teeth (Oligodontia).